The Behavioral Analysis and Financial Performance of Individual Investors at Pakistan Stock Exchange - Mahmood, Tahir; Ayyub, Rana Muhammad; Imran, Muhammad; Naeem, Saira; Abbas, Waseem (International Journal of Economics and Financial Issues, 2020)
This study examines the impact of behavioral factors over investment decision making and their performance. The primary data set collected through survey questionnaires from active investors of Pakistan stock exchange was used for the analysis. Furthermore the study analyzed the role of financial literacy as a moderator variable between behavioral factors and investment decision making as the financial literacy help investors to avoid behavioral biases and make the rational decision that increase their wealth. Collected data are analyzed by using AMOS software to test the hypotheses. The analysis shows that behavioral factors including Heuristic, Prospect, Market and Herding have found highest strong impact on investment decision making of investors. The findings of the study reveal that Prospect and herding have positive impact on investment performance whereas heuristic and market variable has negative impact on investment performance. The results indicate that financial literacy enhanced the relationship between behavioral factors (heuristic, prospect, market) and investment decision making of investors and lessened the relationship with herding variable and investment decision making. The analysis of this study is expected to contribute significantly in the development of the field of behavioral finance. Keywords: Behavioral factors, Investment decisions, Investment performance, Pakistan Stock Exchange. JEL Classifications: G, G01 DOI: https://doi.org/10.32479/ijefi.10112